Healthcare utilization and outcomes in atrial fibrillation ablation patients with and without insertable cardiac monitoring. (25th November 2020) - Mansour, M.C; Gillen, E.M; Garman, A; Rosemas, S; Ziegler, P.D; Pines, J.M
Abstract: Background: Atrial fibrillation (AF) is associated with increased risk of stroke and progression to heart failure, and as a result, increased mortality. Catheter ablation can reduce AF burden, potentially allowing discontinuation from anticoagulant medication in some patients. Post ablation, guidelines recommend ECG monitoring in patients discontinuing anticoagulation to monitor potential AF recurrence. Short-term ECG monitors have lower detection rates for AF recurrence, while long-term insertable cardiac monitors (ICM) increase detection rates and the opportunity to manage and treat AF, when it recurs. Whether more intensive monitoring via ICMs translates to improvements in health outcomes or reduced costs is not well understood. Purpose: We examined healthcare utilization/costs and anticoagulant discontinuation following AF ablation, in patients with vs. without ICM. Methods: Patients with a catheter ablation for AF between January 1, 2011 - March 31, 2018 were identified in a large U.S. administrative claims database. Patients with ICM implant within 1 year pre- or post-ablation were propensity score matched to patients without ICM, based on: demographics, comorbidities, CHAD2S2-VASc score, medication use and healthcare costs in baseline. Results: A total of 691 ICM patients were identified and matched 1:3 with 2, 073 non-ICM patients. Mean age was 65 years, 38% were female, and mean (SD) CHAD2S2-VASc was 2.29 (1.53). During an average follow-up from ablation discharge of 37 (19) months, ICM patients incurred fewer AF- and HF-related hospitalizations: mean 0.51 (0.91) vs. 0.62 (1.56) AF-related, p=0.018, and 0.14 (0.48) vs. 0.24 (1.30) HF-related hospitalizations per patient, p=0.00. Correspondingly, average per-patient costs for AF- and HF-related hospitalizations were lower in the ICM cohort: 13, 041 (30, 831) vs. 17, 140 (55, 576), p=0.016 and 3, 921 (17, 865) vs. 6, 746 (33, 148), p=0.005. The ICM cohort had a greater number of AF-related clinic visits during follow-up: 14.2 (13.0) vs. 10.2 (11.7) visits per patient, p<0.0001. The proportion of patients undergoing a repeat AF ablation during follow-up was higher in the ICM cohort (22.3% vs. 18.3%, P<0.0001), while the proportion with cardioversions was lower (21.0% vs. 25.1%, p=0.031). In patients indicated for anticoagulation (CHAD2S2-VASc≥2), the rate of anticoagulant discontinuation (defined as gap in coverage ≥90 days) was high in both cohorts: 89.5% and 84.6% of patients in ICM and non-ICM groups, respectively. Conclusions: AF ablation patients with ICM experienced fewer AF- and HF-related hospitalizations/costs and fewer cardioversions during follow-up. The greater number of AF-related clinic visits and repeat AF ablations observed in ICM patients indicate closer management. Of note, anticoagulant discontinuation was similarly high in the non-ICM cohort despite guidelines recommending rigorous cardiac monitoring for AF recurrence in the context of discontinuation. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Medtronic